Utilization of Moringa oleifera L. Extract on the Growth of Allium cepa L. Shoots as a Biological Learning Resource - Siska Dwi Anggraini; Imas Cintamulya (Biocaster : Jurnal Kajian Biologi, 2026)
The utilization of Moringa oleifera L., leaf extract as a natural plant biostimulant has attracted considerable attention; however, its effect on the early growth of Allium cepa L., sprouts remains unclear. This study was conducted to assess the effect of Moringa oleifera L., leaf extract on plant growth of Allium cepa L., sprouts and to explore its potential as a local-potential-based biology learning resource. This research applied an experimental approach using a completely randomized design with four different concentrations of moringa leaf extract (25%, 50%, 75%, and 100%) with six replications. The observed parameters were leaf number and plant height at 5, 8, 11, and 14 Days After Planting (DAP). Data were analyzed using one-way Analysis of Variance (ANOVA) at a 5% significance level. The results indicated that different concentrations of moringa leaf extract had no significant effect on the number of leaves (F = 0,080; p = 0,970) or plant height (F = 1,114; p = 0,367) of Allium cepa L., during the 14-day observation period. Nevertheless, the experimental procedure provides a practical and locally relevant learning resource for teaching plant growth and development concepts as well as scientific inquiry skills in biology education.